2011
DOI: 10.1017/s0007485311000307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and relative humidity on the development and fecundity of Chilo partellus (Swinhoe) (Lepidoptera: Crambidae)

Abstract: The spotted stemborer, Chilo partellus (Swinhoe) (Lepidoptera: Crambidae), is one of the most important insect pests attacking maize and sorghum in Ethiopia. Recent studies have indicated that the pest is spreading to new locations where it was not reported before. In the current study, laboratory investigations were carried out to determine the combined effect of different levels of relative humidity and temperature regimes on the development and fecundity of C. partellus, as these physical factors are known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 27 publications
(47 reference statements)
2
36
0
Order By: Relevance
“…Temperature regimes and different levels of relative humidity are known to play an important role in the life cycle of insect and its adaptability to the local climate (Tamiru et al, 2012). Some researchers believe that the effect of temperature on insects largely overwhelms the effects of other environmental factors (Bale et al.…”
Section: Effect Of Rearing Seasons On Biological and Economical Traitmentioning
confidence: 99%
See 4 more Smart Citations
“…Temperature regimes and different levels of relative humidity are known to play an important role in the life cycle of insect and its adaptability to the local climate (Tamiru et al, 2012). Some researchers believe that the effect of temperature on insects largely overwhelms the effects of other environmental factors (Bale et al.…”
Section: Effect Of Rearing Seasons On Biological and Economical Traitmentioning
confidence: 99%
“…It has been reported that the temperature has highly significant effects on all developmental parameter of insect than humidity and rainfall (Bhat and Bhattacharya, 1978). Developmental time of an insect is inversely related to temperature (Tamiru et al, 2012). Among plants and their interactions (Venugopal and Krishnaswami, 1987).…”
Section: Effect Of Rearing Seasons On Biological and Economical Traitmentioning
confidence: 99%
See 3 more Smart Citations